2009
DOI: 10.1101/gad.1843709
|View full text |Cite
|
Sign up to set email alerts
|

Reduced capacity of alternative σs to melt promoters ensures stringent promoter recognition

Abstract: In bacteria, multiple σs direct RNA polymerase to distinct sets of promoters. Housekeeping σs direct transcription from thousands of promoters, whereas most alternative σs are more selective, recognizing more highly conserved promoter motifs. For σ32 and σ28, two Escherichia coli Group 3 σs, altering a few residues in Region 2.3, the portion of σ implicated in promoter melting, to those universally conserved in housekeeping σs relaxed their stringent promoter requirements and significantly enhanced melting of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
52
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(52 citation statements)
references
References 68 publications
0
52
0
Order By: Relevance
“…Further, it was demonstrated that RpoH from the alphaproteobacterium Caulobacter crescentus recognizes E. coli promoters that lack the extended Ϫ10 motif (29). It has been postulated that by increasing promoter stringency, the extended Ϫ10 motif allows for an efficient response to a restricted set of promoters and that lack of an extended motif may allow alphaproteobacterial RpoH to transcribe larger sets of genes involved in a variety of processes (30). This premise is supported by previous work showing that, in addition to heat shock, S. meliloti rpoH1 is required for response to acid shock and survival in root nodules (10,40,47) and by our current study defining a large set of rpoH-dependent genes.…”
Section: Discussionmentioning
confidence: 99%
“…Further, it was demonstrated that RpoH from the alphaproteobacterium Caulobacter crescentus recognizes E. coli promoters that lack the extended Ϫ10 motif (29). It has been postulated that by increasing promoter stringency, the extended Ϫ10 motif allows for an efficient response to a restricted set of promoters and that lack of an extended motif may allow alphaproteobacterial RpoH to transcribe larger sets of genes involved in a variety of processes (30). This premise is supported by previous work showing that, in addition to heat shock, S. meliloti rpoH1 is required for response to acid shock and survival in root nodules (10,40,47) and by our current study defining a large set of rpoH-dependent genes.…”
Section: Discussionmentioning
confidence: 99%
“…However, the evidence is, in general, weak (Discussion) (9,22,23). Effective experimental tests have been complicated by (i) the general inability of bulk experiments to directly measure promoter binding uncoupled from subsequent conformational changes (2, 24) and (ii) the weak sequence specificity of DNA binding (25,26).…”
mentioning
confidence: 99%
“…However, the evidence is, in general, weak (Discussion) (9,22,23). Effective experimental tests have been complicated by (i) the general inability of bulk experiments to directly measure promoter binding uncoupled from subsequent conformational changes (2, 24) and (ii) the weak sequence specificity of DNA binding (25,26).In a previous study (7), we used colocalization single-molecule spectroscopy (CoSMoS) to directly observe and measure the initial rate of binding of σ 54 RNAP to a cognate promoter uncoupled from subsequent conformational isomerization of the polymerasepromoter complex. We also showed that the initial RNAPpromoter complex that we observe is on the pathway to transcription initiation.…”
mentioning
confidence: 99%
“…The GCCG motif is a composite recognition element: the GC is recognized by R91 from region 3 of E. coli 28 (the D ortholog), whereas the CG is recognized by R84 and D81 from region 2.4 (14). The corresponding residues in R91 recognizes a G residue at either of the first two positions of the extended Ϫ10 element (15), and D Ap R104 is therefore predicted to contact G on the template strand at position Ϫ14 (Fig. 2).…”
mentioning
confidence: 99%